Impacts of Circular Frame Fixator (Ilizarov) on Management of Compound fractures of proximal tibia - Saifullah Soomro, Zamir Ahmed Soomro (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the outcome of patients diagnosed with complex fractures of tibial plateau with associated soft tissue compromise treated by using Ilizarov fixator. Study design: Prospective observational study. Place and period of study: Orthopaedic unit, Chandka Medical College SMBBMU Larkana from January 2021 to December 2021 Methods: Patients diagnosed with complex tibial plateau fracture with associated soft tissue compromise fulfilling inclusion criteria were enrolled in study. All participants were managed with Ilizarov fixator and it was removed when fracture was united clinically and radiologically. Outcome of patients was evaluated on the basis aggregate score of knee society score and knee functional score at 6month follow up. Results: Twenty seven consecutive patients met the inclusion criteria, of which 19(70.37%) were male and 8(29.7%) were female. Average age of patients was 32.37 years. All fractures healed by the end of the 4th month. Ring fixator was removed routinely at 16th weeks after initial surgery in all patients. Transient peroneal nerve injury was found in 2 patients; no patients developed deep vein thrombosis, whereas pin site infection was most common complication and occurred in 5 patients (18.5%). According to knee society score results were excellent in 15(55.55%) patients, good in 08(29.62%) patients, fair in 03(11.11%) in patients and poor in 01(3.70%) patient. Practical implication most of proximal tibial plateau fractures with soft tissue compromise are kept under observation till the soft tissue status become favorable for open reduction and internal fixation, while fixing these type of fracture with Ilizarov fixator one can provide early relief to patients and results of this study will be help for operating surgeons while managing complex proximal tibia fractures. Conclusion: complex tibial plateau fracture can be effectively treated with Ilizarov fixation method without any complication, when exposed reduction and interior fixation with plate is contraindicated due to compromised soft tissue. Keywords: Tibial plateau, fractures, Ilizarov, fixation method, outcome, soft tissue compromise